2019
DOI: 10.4274/turkderm.galenos.2019.82612
|View full text |Cite
|
Sign up to set email alerts
|

The effects of topical liposomal resveratrol on incisional and excisional wound healing process

Abstract: Background and Design: The objective of this study was to investigate the wound healing activity of different concentrations of liposomal trans-resveratrol formulations on incisional and excisional wounds in rats. Materials and Methods: The wound healing effect was tested by an excisional and incisional wound model. Wound closure was measured for 12 days. On the 12 th day of the study, maximal load, maximum stress, stress, and % of elongation values were evaluated in the incisional wound. In addition, angiogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Liposome carrier systems were designed by thin film preparation method (Gunal et al, 2019). Firstly, liposome dispersions (HSP and Cholesterol) were designed by dissolving the 40 μmol mL −1 of phosphatidylcholine and lipophilic components in 30 mL chloroform in a round flask.…”
Section: Preparation Of Herbal Liposome Formulationsmentioning
confidence: 99%
“…Liposome carrier systems were designed by thin film preparation method (Gunal et al, 2019). Firstly, liposome dispersions (HSP and Cholesterol) were designed by dissolving the 40 μmol mL −1 of phosphatidylcholine and lipophilic components in 30 mL chloroform in a round flask.…”
Section: Preparation Of Herbal Liposome Formulationsmentioning
confidence: 99%
“…Wound healing is not a stationary process, so the stages mentioned above may overlap. 2,3 Many factors influence the wound healing progress and any disruption may lead to defective tissue reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that nanocomposite hydrogels used for wound treatment exhibited significant inhibition against Gram-positive and Gram-negative bacteria due to Ag + ions released from silver nitrate [ 8 , 9 , 10 ]. Another readily used wound healing material is, for example, honey extract, which improves wound removal and cell proliferation, leading to faster closure of wound edges [ 11 , 12 , 13 , 14 , 15 ]. It is also beneficial due to its high sugar content, which creates a higher osmotic gradient that pulls fluid through the subdermal tissue and provides an additional source of glucose for the growth of cellular components in the wounded area [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has a strong antioxidant, anti-inflammatory, antifungal and antibacterial effect as well as cardio- and neuroprotective properties [ 14 ]. Numerous studies also show its effectiveness against skin, prostate, lung, colon and liver cancer cells [ 15 , 16 ]. Furthermore, resveratrol has the ability to induce cell proliferation and accelerate wound closure in in vivo models in studies conducted on rats [ 21 ].…”
Section: Introductionmentioning
confidence: 99%